The un-friendship bracelet - Maker, Martha (Craftily ever after, 2018)
"Best friends Emily and Maddie have one big thing in common: they love to craft and create! Whether it's making art with balloons, cities of cardboard and straws, or the matching friendship bracelets they wear, they're always coming up with fresh ideas. But when a new student named Bella shows up at school, their friendship is put to the test. Maddie immediately befriends her and discovers that Bella is just as crafty as she and Emily are! As Maddie and Bella spend more time together, Emily finds herself spending more time alone. Then, when Emily's friendship bracelet falls off, she begins to think that maybe it was an un-friendship bracelet this whole time. Will the friends find their craftily ever after?"--Page 2 of cover.